Estudo do polimorfismo do ácido palmítico sob variação da polaridade do solvente - ABREU, Diego Coelho (2018)
Palmitic acid (PA) is a saturated fatty acid with a molecular structure CH3-(CH2)14- COOH, commonly found in animal and vegetable fats. It can crystallize in the Atriclinic, Bo, Bm, C, Eo and Em forms with crystalline triclinic, orthorhombic and monoclinic systems. In this study, polycrystalline samples of PA were obtained from the technique of slow evaporation in solvents with different polarities. The characterization of these polymorphic crystals was performed using Raman spectroscopy and infrared, as well as differential scanning calorimetry (DSC) and X-ray diffraction (XRD), the parameters obtained in the XRD were refined using the Rietveld method. According to the results, the crystals formed using polar solvents with high evaporation rate form crystals with the phases Em and C. Forms Bm e C are predominant for polar solvents with low evaporation rate and in nonpolar solvents. The Raman spectra of the samples obtained from nonpolar and polar solvents with low evaporation rate indicate shifts in lattice modes for larger wave numbers, which may be associated with an elongation at the hydrogen bonds (O−H...O). Bands around 1700 cm-1, associated with the vibration of the group C = O are presented as singlets for polar samples with high evaporation rate; Mode around 1700 cm- 1, associated with the vibration of the group C=O are presented as singlets for polar samples with high evaporation rate; and as doubts to the others. The spectra obtained in the infrared show the same behavior observed in the Raman spectra, indicating that the samples obtained in nonpolar or polar solvents with low evaporation rate, showing different phases of the other samples. The DSC analysis shows the occurrence of thermal events in the samples of polar solvents with low evaporation rate and nonpolar before melting, concerning the transformation BmC. The XDR in high temperature confirms the data obtained with thermal analysis and shows a preferential thermal expansion in the plane (020). Thus, it is evident that the polarity of the solvent directly influences the PA polymorphism, the evaporation rate of the solvent can also be included as a relevant factor in this phenomenon.